2022
DOI: 10.3390/en15020507
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Techniques for Power System Transient Stability Assessment

Abstract: The high penetration of renewable energy sources, coupled with decommissioning of conventional power plants, leads to the reduction of power system inertia. This has negative repercussions on the transient stability of power systems. The purpose of this paper is to review the state-of-the-art regarding the application of artificial intelligence to the power system transient stability assessment, with a focus on different machine, deep, and reinforcement learning techniques. The review covers data generation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…ML is further divided into supervised learning, unsupervised learning, and reinforced learning for use in power electronics. Some of the research trends and an overview of artificial intelligence in power electronics can be found in [22][23][24][25][26][27][28][29][30].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…ML is further divided into supervised learning, unsupervised learning, and reinforced learning for use in power electronics. Some of the research trends and an overview of artificial intelligence in power electronics can be found in [22][23][24][25][26][27][28][29][30].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…The scientific area that examines this effort is called "Artificial Intelligence" (AI) and can be considered as a computer science branch which is divided into many subareas due to the recent surge in research on this field. Figure 1 illustrates the sub-branches of AI [20][21][22][23][24]. The basic concept of AI is the description and the design of agents that receive stimuli from the environment and perform actions.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…A review paper [4] discusses broader aspects of the artificial intelligence applications to the power system transient stability assessment. The review covers data generation processes (from wide-area measurements as well as from simulations), data processing pipelines (features engineering, splitting strategies, dimensionality reduction, embedding, encoding), model building and training (including ensembles and hyperparameters optimization techniques), deployment, and management (with monitoring for detecting bias and data drift).…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%